1997
DOI: 10.1016/s0006-3495(97)78677-6
|View full text |Cite
|
Sign up to set email alerts
|

Binding to phosphatidyl serine membranes causes a conformational change in the concave face of annexin I

Abstract: Recent studies have revealed that binding of annexin I to phospholipids induces the formation of a second phospholipid binding site. It is shown that the N terminus on the concave side of membrane-bound annexin I is cleaved much faster by trypsin or cathepsin than the N terminus of the free protein. The reactivity of the unique disulfide bond located near the concave face was similarly increased by membrane binding. These results demonstrate that Ca(2+)-dependent membrane binding induces a conformational chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…Proteolysis of annexin 1 bound to phosphatidylserine-vesicles was almost complete after one minute, whereas about 30 minutes were required to cleave annexin 1 in solution. 17,19 Combining the results from these publications, it seems likely that annexin 1 binds to membranes containing negatively charged phospholipids first. This binding event is calcium-dependent, and involves the convex site of the molecule using calcium ions as bridges between the annexin and the bilayer.…”
Section: Membrane Interaction Of the Annexin 1 N-terminal Domainmentioning
confidence: 84%
See 2 more Smart Citations
“…Proteolysis of annexin 1 bound to phosphatidylserine-vesicles was almost complete after one minute, whereas about 30 minutes were required to cleave annexin 1 in solution. 17,19 Combining the results from these publications, it seems likely that annexin 1 binds to membranes containing negatively charged phospholipids first. This binding event is calcium-dependent, and involves the convex site of the molecule using calcium ions as bridges between the annexin and the bilayer.…”
Section: Membrane Interaction Of the Annexin 1 N-terminal Domainmentioning
confidence: 84%
“…Interestingly, this secondary binding site exhibits neither calcium dependency nor lipid specificity. 9,13,[18][19][20] These data suggest that the N-terminal domain of annexin 1 alone might provide a second membrane-binding site. This hypothesis is supported by a publication from Lee and co-workers in which they present data that a peptide comprising residues 1-26 of annexin 1 alone is able to form an α-helix in 50% trifluorethanol (TFE)/water and 10 mM sodium dodecyl sulfate (SDS), suggesting membrane binding activity.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on annexin I-induced membrane aggregation indicated the presence of an inducible secondary interaction site for membrane aggregation that is distinct from the primary membrane-binding site (19,28,29,35,36). Three major topological models of annexin I-mediated membrane aggregation, which are based on the presence of the inducible secondary interaction site, are depicted in Figure 1, panels a-c. Each model could also involve the lateral association of membrane-bound annexin molecules, as shown in Figure 1, panels d-f.…”
Section: Models Of Annexin I-induced Membrane Aggregationmentioning
confidence: 99%
“…9 The calcium-and membrane-binding sites are located on the convex face but additional phospholipid-binding sites have been described for the N-terminal domain located on the concave face (annexin A1). 10,11 The N-terminal domains of annexins are highly variable and confer specific properties to each particular annexin. The alpha-giardins have been classified as representatives of a new annexin subfamily (annexin E family) due to their low but significant sequence identity with annexins from other organisms, but to date no three dimensional structure has been determined for any alphagiardin.…”
Section: Introductionmentioning
confidence: 99%